Sistematična analiza decentraliziranih družbenih medijev (University of Maribor Press, 2024)
A Systematic Analysis of Decentralised Social Mmedia. The monograph "A Systematic Analysis of Decentralised Social Media" addresses a recognised research gap in the study of decentralised social media. In doing so, particular emphasis is placed on the conceptual aspect, which allows for the identification of the logical design, architectural features, potentials and specificities of decentralized social media and comparison with their centralised competitors. It is a collection of inter-comparable chapters that descriptively and analytically examine the most prominent representatives of the landscape of decentralised social media in 2024. The chapters are the result of a project assignment of students from the University of Maribor, Faculty of Electrical Engineering, Computer Science and Informatics, who systematically and under supervision studied selected decentralised social media in the framework of the course "Social Media Architectures".